2019
DOI: 10.1371/journal.pone.0226371
|View full text |Cite
|
Sign up to set email alerts
|

Examining practice effects in repeated measurements of vibration perception thresholds on finger pulps of healthy individuals – Is it possible to improve your results over a clinically relevant test interval?

Abstract: AimsTo investigate practice effects in a test-retest situation, where vibration perception thresholds (VPT) were measured in healthy subjects using a multi-frequency test method.MethodsIn eight consecutive tests, VPTs were tested in the pulps of the index and little fingers at seven frequencies (8, 16, 32, 64, 125, 250 and 500 Hz). Subjects were twenty healthy adults aged 26 to 65 years (mean 46.0 ± 11.1 years; 10 male and 10 female). The subjects were examined at six tests with intervals of one month (mean 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Clinical implications that follows our study are for example to facilitate follow-ups of nerve affecting disorders in both primary and diabetic care, as well as to constitute a useful tool in neuropathic investigations. Impact of repeated measurements has been evaluated and the results implicated that practice effects are non-existing when examining VPTs through vibrometry at an annual basis [ 46 ]. If applicable, the possibility to compare subjects to their own former results would therefore be an important tool in these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical implications that follows our study are for example to facilitate follow-ups of nerve affecting disorders in both primary and diabetic care, as well as to constitute a useful tool in neuropathic investigations. Impact of repeated measurements has been evaluated and the results implicated that practice effects are non-existing when examining VPTs through vibrometry at an annual basis [ 46 ]. If applicable, the possibility to compare subjects to their own former results would therefore be an important tool in these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a quantitative method, with good reliability as a reference, creates a problem. The VibroSense Meter has good test-retest reliability [25,26] without any practice effect. We have recently shown that it is sensitive enough to be used to monitor the effects of improved metabolic control on nerve function [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, VPT was tested at a total of 28 (4×7) frequencies. The performance of the VPT test has been published in two studies applying similar test equipment and methods 21 22. The participants had at least a 3-hour exposure-free period before the test and were asked not to use tobacco in any form the last hour before the test.…”
Section: Methodsmentioning
confidence: 99%